Influence of Stakeholder Participation on Performance of Rice Sector in Kenya - Karanja, Francis Njoroge; Kagiri, Assumpta; Paul, Samson Nyang’au (International Journal of Leadership and Governance, 2025)
Purpose: The purpose of this study is to determine the influence of stakeholder participation on performance of rice sector in Kenya. Methodology: The study was anchored on the stakeholder theory .The target population of this study comprised of 185 farmer representatives (cooperative managers), 36 staff of research institutions (researchers) and 9 managers of National Irrigation Authority and 16 rice millers (managers) as the key stakeholders of rice growing in Kenya. The study sample size was 152 and study adopted multi-stage sampling whereas purposive, stratified and random sampling techniques were appropriate for drawing sample size. The data collection instruments were questionnaires and interview schedules. The qualitative data was analyzed by use of the content analysis. While quantitative data was analyzed using SPSS Version 27. Both descriptive and inferential statistics were established. Findings: The study revealed that stakeholder participation has a statistically positive and significant relationship with rice sector performance. The descriptive results indicated that majority of the respondents (mean =3.91, standard deviation =1.048) implied that stakeholder participation was among the stakeholder governance mechanisms employed in the rice sector in Kenya. The correlation results also revealed that stakeholder participation and performance of rice sector in Kenya were positively and significantly related (r=0.810, p=0.000). In addition, the regression results showed that stakeholder participation explains 65.7% of the variations in performance (r-squared =0.657), making it a strong predictor of performance in Kenya's rice sector. The regression model was statistically significant (F = 234.042, p < 0.05), and stakeholder participation had a positive and significant effect (β=1.034, p=0.000) on performance of rice sector in Kenya. Unique Contribution to Theory, Practice and Policy: The study recommends that managers in the rice sector actively engage all stakeholders farmers, government agencies, development partners, and local communities in decision-making processes. This is through implementing regular stakeholder meetings, surveys, and feedback mechanisms to ensure that stakeholders' voices are heard.